International initiatives for the study of the human brain: EBRAINS and its Spanish node - Teris Duran; David Ezpeleta; Gemma Aragonès; Javier Mínguez; Emma Muñoz-Moreno; Maria V. Sanchez-Vives; Guillermo Velasco (Kranion)
The present article provides an overview of the main global initiatives that have emerged around the human brain in the last century, the achievements made, the most relevant technological capabilities, in what aspects they differ from other projects and the strategic vision of Europe in this neurotechnological era. EBRAINS, as a digital research infrastructure in neuroscience and legacy of the Human Brain Project, shares a broad catalogue of services, platforms and technologies inspired by medicine, mental health, data science, simulation, brain atlases, among others; powered by an innovative and vibrant interdisciplinary community distributed across more than its 243 partner institutions. Moreover, the global challenges on neurological and mental disorders, their incidence and prevalence, increasingly require R&D projects directed towards translational and personalized medicine. In an effort to advance these approaches, EBRAINS offers the medical and research sector tools such as The Virtual Epileptic Patient, The Virtual Brain, Medical Informatics Platform, Perturbational Complexity Index, Virtual Research Environment, among others; with the potential to move to clinical practice in the future, as well as other innovations in the spectrum of consciousness disorders or blindness. The Spanish node of EBRAINS, coordinated by the Polytechnic University of Madrid, is presented. By late 2024, it comprises thirteen institutions from the public and the private sector. Representative cases of the triad university, business and research centre are described, considering their trajectory since HBP, together with some of their most inspiring projects.